Nonlinear analysis of masonry panels strengthened with textile reinforced mortar. (15th April 2016) - Basili, M.; Marcari, G.; Vestroni, F.
Highlights: Modelling approach for the analysis of reinforced masonry panels with basalt textiles. Macroscopic smeared crack approach assumed for the unreinforced and reinforced panels. Sensitivity analyses carried out to investigate the influence of each parameter. Representative numerical models for the unreinforced and the reinforced panels defined. Numerical-experimental comparisons to investigate models feasibility. Abstract: The paper proposes a simplified modelling approach for the analysis of the in-plane shear behavior of tuff stone masonry panels strengthened with a surface bonded composite Basalt Textile Reinforced Mortar (BTRM) system subjected to diagonal compression. The nonlinear behavior of the unreinforced and reinforced panels is reproduced by means of a macroscopic smeared crack approach. The masonry is modeled as an isotropic continuum material characterized by different nonlinear softening laws in tension and compression. The BTRM composite is modeled with two layers representing the basalt textile and the matrix with different constitutive relationships. Sensitivity numerical analyses are developed in order to investigate the influence of each parameter in the global nonlinear response of the panel. Then, representative numerical models for the unreinforced and the reinforced panel are presented. Two BTRM layouts are investigated: single-side and double-side reinforcement. The models aim to capture the main aspects of the observed experimental nonlinear response, such as stiffness, strength-deformation shear capacity and failure mechanism. The numerical results are compared with the experimental outcomes of diagonal compression tests to investigate the feasibility of the models in the description of the in-plane shear behavior of tuff stone panels strengthened with the BTRM system.